Introduction of a digital maturity assessment framework for construction site operations. Issue 5 (4th April 2023) - Wernicke, Brian; Stehn, Lars; Sezer, Ahmet Anil; Thunberg, Micael
Abstract: Digital technologies as enablers for more sustainable improvements of construction site processes contain interesting opportunities. Little is known how to, in a structured way, assess and implement digital technologies to support development and improvement of construction site operations. Maturity frameworks assess the status quo and guide decision makers to potential improvements. The purpose of this research is to develop a framework for assessing digital maturity of construction site operations. Literature and empirical data were utilized to develop and validate the framework. The framework contains assessment areas that specify the areas of potential improvements, maturity levels that indicate the progression towards maturity, assessment criteria that define organizational aspects of the assessment, and an assessment procedure to guide assessors. The maturity assessment framework contributes potentially to systematization of evaluative processes creating opportunities for a change within processes and organizations enabled by digital initiatives and to long-term improvements on project portfolio level.